Enhanced cooling performance of magnetic nanofluids in tri-coaxial tube heat exchangers with magnetically induced swirling flow - Gaur S.K.; Sahoo R.R. (My University, 2025)
This study uses numerical simulations to investigate magnetic nanofluid cooling dynamics in a counter-current tri-coaxial tube with a circular and triangular annular-based heat exchanger with a homogeneous magnetic field. The study incorporated a magnetic source term into the y-momentum equation. It used ANSYS Fluent, a custom User Defined Function (UDF) created in C++, to describe how the properties of nanofluids changed in response to temperature changes and the Brownian effect. Simulations span a Reynolds number range from 200 to 1800, with magnetic field intensities of 400G, 800G, and 1600G and nanoparticle volume fractions of 1%, 2%, and 3%. The study reveals that the benefits of magnetic field application are most pronounced at lower Reynolds numbers, high magnetic intensity, and 3% nanoparticle concentration in configurations with a triangular inner annulus, where cooling occurs at an early stage compared to circular tubes. Nanofluid alone achieves a maximum enhancement of 47% in heat transfer coefficient (HTC). Still, a substantial increase in HTC—up to 257% at the highest magnetic intensity—correlates with a 30% rise in pumping power compared to base fluid without magnetic intensity, illustrating a favorable balance between energy input and heat transfer enhancement. The study also noted changes in flow patterns due to magnetic intensity, where the swirl velocity vector and helical trajectories traced by nanoparticles rupture the boundary layer, facilitating a uniform radial distribution of temperature across each slice of the heat exchanger. The findings underscore the potential of magnetic fields in significantly boosting the thermo-hydraulic factor (THF)—up to 22.32%, HTC—up to 13.7%, and Normalized Nu—up to 12% for triangular shape as compared to circular one at the same configuration, offering valuable insights that prove the triangular shape is more effective in all assessed aspects, particularly in its interaction with magnetic fields to enhance heat transfer. © 2025 Elsevier Ltd